Assessment of Coronary Heart Disease Risk Among Medical Faculty Members Using The Jakarta Cardiovascular Score (JAKVAS) - Wicaksono, Michael Geoffrey; Burahman, Habib; Lestari, Yani Dwi (Journal of Health and Nutrition Research, 2025)
Coronary heart disease (CHD) is a condition caused by the narrowing of the coronary arteries, leading to reduced blood flow to the heart. It is the leading cause of death globally and continues to increase, particularly in developing countries such as Indonesia. In Banten Province, the prevalence of heart disease is reported at 1.4%. Unhealthy lifestyle habits among the general population, including those within academic communities, can raise the risk of CHD and negatively impact quality of life. This study aimed to detect early CHD risk using the Jakarta Cardiovascular Score (JAKVAS) among the academic community of FKIK UNTIRTA to raise awareness and encourage preventive measures. An analytical observational method with a cross-sectional study design was employed. Consecutive sampling was used to assess the relationship between CHD risk factors listed in the JAKVAS as independent variables and CHD risk as the dependent variable. The results showed that 86.7% of the academic community at FKIK UNTIRTA were in the low-risk category, 4.44% in the moderate-risk category, and 8.89% in the high-risk category. The proportion of respondents with high blood pressure was 25.6%, BMI ≥26.00 was 23.3%, smoking history was 20%, diabetes mellitus history was 5.6%, and those aged over 49 years and male were 13.3%. A significant relationship was found between increased CHD risk and factors such as age, gender, blood pressure, BMI, smoking history, and diabetes mellitus. Among these, smoking history (OR 14.458) and BMI (OR 6.685) were the most dominant risk factors. These findings suggest the need to improve awareness among the population regarding cardiovascular health and promote the adoption of healthier lifestyles to reduce future risk.